Practical Rails social networking sites - Bradburne, Alan.; SpringerLink (Online service) (Berkeley, CA : Springer, 2007)
Provides information on creating online social networking sites using Rails.
Includes index.
Keywords: Ruby on rails (Electronic resource); Web site development; Online social networks